Predictive value of the milking patency test when performing the arterial microanastomosis in head and neck surgery. Issue 9 (22nd June 2019) - Podeur, Fabien; Peyrachon, Benjamin; Nokovitch, Lara; Dammacco, Maria Adèle; Qassemyar, Quentin; Deneuve, Sophie
Abstract: Background: The milking patency test (MPT) is widely used to assess the patency of microanastomosis, despite it being proven to be a traumatic test. Methods: We performed microanastomoses with intentional two‐wall stitches and asked senior microsurgeons to evaluate the permeability of the anastomoses by looking first at the results of the MPT, then according to artery pulsation. Results: Microsurgeons were all accurate in evaluating normal or clamped anastomoses. But in anastomoses with defects, the MPT was considered normal 94%, 85%, and 73%. MPT has a positive predictive value of 100% but with a negative predictive value of 27.5%. Observation of the artery pulsation distal to the anastomosis gave similar results. Conclusions: Our experiment shows that the two‐wall stitches on arterial anastomoses are hardly detected by an MPT. The observed pulsation of the artery gives the same results and could be used instead, without damaging the vessels.